The relative age effect among female Brazilian youth volleyball players - Okazaki, F. H. A.; Keller, B.; Fontana, F. E.; Gallagher, J. D. (Research Quarterly for Exercise and Sport, 2011)
In sports, the relative age effect (RAE) refers to performance disadvantages of children born late in the competition year compared to those with birthdays soon after the cutoff date. This effect is derived from age grouping, a strategy commonly used in youth sport programs. The purpose of age grouping is to decrease possible cognitive, physical, and emotional differences among sport participants. In spite of the efforts to equate playing conditions, youth athletes born early in the competitive age group are selected to be part of squads more often than late-born athletes, even within the same 1-year category.